Penerapan Rebusan Daun Sirih Merah terhadap Proses Penyembuhan Luka Perineum pada Ibu Post Partum Spontan di Bidan Balai Desa Kedungwaduk - Putri Ayu Maharani; Ida Nur Imamah (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Background: In 2020, there were 2.9 million cases of perineal rupture in mothers giving birth, it is estimated that this will reach 6.8 million in 2050. Childbirth is a process that is vulnerable to various complications that can endanger the mother. Vaginal delivery is more susceptible to tearing of the perineum to varying degrees. Red betel leaves contain essential oils, hydroxycabicol, chabicol, carbibetol, allylcatechol, cineole, tanim, diastase, sugar and starch. Objective: to determine changes in wound healing before and after being given red betel leaf decoction Method: Case study with application to 2 respondents. Respondents were given red betel leaf decoction twice a day in the morning and evening for 5 consecutive days. Wounds were measured using the REEDA scale. Results: After applying red betel leaf decoction, the results showed a decrease in the rate of wound healing in both respondents, there was a decrease in scores from previously Mrs. E 10 becomes 0 (good wound healing) and Mrs. S 11 becomes 1 (poor wound healing). Conclusion: There were changes and differences in the rate of wound healing before and after giving red betel leaf decoction to the two respondents. Keywords: , ,